Continuous Performance Validation: A Framework for Automated Testing Integration in Enterprise DevOps Pipelines - Santhosh Kumar Shankarappa Gotur (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article presents a comprehensive framework for integrating automated performance testing within modern DevOps pipelines, addressing the growing complexity of continuous software delivery while maintaining performance standards. The article introduces a systematic approach combining shift-left testing methodologies with microservice-level performance validation, enabling early detection and resolution of performance issues throughout the development lifecycle. Through an article analysis of contemporary testing tools and methodologies, the article proposes a multi-layered testing strategy encompassing continuous performance testing, load simulation, and chaos engineering practices. The framework incorporates automated feedback loops, real-time analytics, and dynamic baseline comparisons, ensuring consistent performance monitoring across development stages. The findings demonstrate that implementing this automated testing framework significantly improves system reliability, reduces performance regression incidents, and enhances overall application resilience. The article also addresses critical challenges in test data management, environment parity, and resource optimization, providing practical solutions for organizations adopting automated performance testing in their DevOps practices. This article contributes to the evolving field of DevOps by offering actionable insights and methodologies for maintaining high-performance standards in modern software development environments.